A Model for Central Bank Digital Currencies: Implications for Bank Funding and Monetary Policy - Jonathan Schiller; Jonas Gross (ZBW - Leibniz Information Centre for Economics, 2021)
Central bankers express concerns that central bank digital currencies (CBDCs) might disintermediate commercial banks and facilitate bank runs. We analyze these concerns in a DSGE framework and provide a rationale for the disintermediation of the banking sector. Our focus is on the central bank's options to counteract the adverse effects of losses in bank funding depending on different CBDC designs. We find that the central bank can stabilize the financial sector by acting as a lender of last resort or by actively governing demand for CBDC.
Keywords: D53; E42; E58; G21; 330; CBDC; financial stability; monetary policy; disintermediation; DSGE